Peran Rumah Qur’an Raudlatusaadah Dalam Memperbaiki Bacaan Qur’an Anak-Anak Di Kelurahan Muara Lakitan - Husna, Jannatul; Arikarani, Yesi (El-Ghiroh : Jurnal Studi Keislaman, 2022)
The importance of learning the Qur'an starts from childhood and there are still many children who have not been able to read the Qur'an properly and correctly in accordance with predetermined rules. This study aims to determine the method used by Rumah Quran Raudatusaadah in teaching the Qur'an and to find out the role of Rumah Quran Raudatusaadah in Improving Children's Quran Reading in Muara Lakitan Village. From the results of the dedication at Rumah Quran Raudatusaadah, it was concluded that the methods used by Rumah Quran Raudatusaadah in teaching the Qur'an in Muara Lakitan were the Talaqq method, the At-Tibyan method and the Tilawati method. The role of Raudatusaadah Quran House in Improving Children's Quran Reading in Muara Lakitan Village is as a new forum for improving Al-Quran reading, and also facilitating the entire process of implementing Al-Qur'an learning activities which aim to provide students with a basic understanding of how to how to read the Qur'an properly and correctly so that in practice the students do not make mistakes in reading the Qur'an, the purpose of this learning is to provide insight to the students so that they are even better at mastering reading the Qur'an. and raise the awareness of the students to be developed so that they can memorize the Qur'an.